2011
DOI: 10.1002/mus.22070
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum interleukin‐17 levels in patients with myasthenia gravis

Abstract: It has been suggested that interleukin-17 (IL-17) plays a crucial role in the development of several autoimmune diseases. However, there are no data about the relationship between myasthenia gravis and IL-17. The aim of this study was to measure the concentration of IL-17 and determine whether levels depend on the severity of MG. Serum IL-17 concentrations were measured in 25 patients. IL-17 concentrations were higher in generalized MG compared with controls and correlated with anti-acetylcholinesterase recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 13 publications
3
47
1
Order By: Relevance
“…The role of Th17 cells in the pathogenesis of autoimmune diseases and MG has been indicated in several studies [22,24,25]. Other studies have revealed that numbers of Th17 cells and associated cytokines such as IL-17 are increased in patients with MG and in animal models; this is consistent with our finding [26,27,28,29]. We also found that Th17 cell numbers were significantly decreased when compared to measurements taken 6 months after TE.…”
Section: Discussionsupporting
confidence: 83%
“…The role of Th17 cells in the pathogenesis of autoimmune diseases and MG has been indicated in several studies [22,24,25]. Other studies have revealed that numbers of Th17 cells and associated cytokines such as IL-17 are increased in patients with MG and in animal models; this is consistent with our finding [26,27,28,29]. We also found that Th17 cell numbers were significantly decreased when compared to measurements taken 6 months after TE.…”
Section: Discussionsupporting
confidence: 83%
“…Experiments with gene-deficient mice indicate that Th17 cells and IL-17 play a crucial role in the pathogenesis of EAMG [23,24]. Moreover, previous studies have shown that serum IL-17 concentrations were higher in MG patients compared with controls and correlated with antiAchR antibody titers [25,26].…”
Section: Discussionmentioning
confidence: 97%
“…Th17 cells in turn secrete the cytokine IL-17A32, and a recent study found that plasma levels of IL-17A were increased in MG patients and that higher levels of IL-17A correlated with greater severity of the disease34. Furthermore, another study presented evidence that serum levels of IL-17 correlates with the AChR antibody titre35. IL-17C, another member of the IL-17 family, has not previously been linked to MG.…”
Section: Discussionmentioning
confidence: 99%